Determinants of revolt: Evidence from survey and laboratory data - Klaus Abbink; Silvia Pezzini (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2005)
This paper examines determinants of revolutionary behaviour. We study the role of freedom of communication, repression of opposition and the government's selfishness. Combining econometric analysis of survey data with a laboratory experiment, we analyse how these factors affect preferences for revolt and revolutionary action. We introduce an experimental game capturing essential features of a dictatorship. The results show that the feeling that the government operates selfishly increases both revolutionary preferences and actions. Political repression and lack of communication freedom increase revolutionary attitudes but decrease actual opposition, consistent with the collective action problem faced by opposition to a dictatorship.
Keywords: C23; C92; D74; H11; 330; Conflict; revolutions; experimental economics; surveys; Politische Unruhen; Test; Public Choice; Schätzung; Welt